Preparation method of dextran microspheres and prepared dextran microspheres

By adding crosslinking agents and optimizing reaction conditions, dextran microspheres with good morphology, uniform particle size and slow degradation were prepared, which solved the problems of environmental pollution, uneven particle size and degradation fragments in the prior art, and improved the biosafety and clinical application prospects of microspheres.

CN119587487APending Publication Date: 2025-03-11YOULEKANG (HUZHOU) MEDICAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411529801.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing methods for preparing dextran microspheres have problems such as environmental pollution, uneven particle size, agglomeration and decomposition after degradation, which affects its therapeutic effect and resilience.

Method used

A crosslinking agent was added by a two-step method, first the crosslinking agent was added to the aqueous phase, and then the aqueous phase was mixed with the oil phase, and then the crosslinking agent was added. Combined with the optimized concentration of sodium hydroxide aqueous solution, dextran concentration and oil-water ratio, the crosslinking temperature and time were controlled to prepare dextran microspheres with good morphology, uniform particle size and slow degradation.

Benefits of technology

The preparation of dextran microspheres without pollution, uniform particle size, and not easy to agglomerate is achieved, which extends the degradation time of microspheres and improves its biosafety and clinical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110206400000101
    Figure BDA0005110206400000101
  • Figure HDA0005110206410000011
    Figure HDA0005110206410000011
  • Figure HDA0005110206410000012
    Figure HDA0005110206410000012
Patent Text Reader

Abstract

The invention discloses a dextran microsphere preparation method, which comprises: S1, preparing a sodium hydroxide aqueous solution containing a cross-linking agent I and dextran to obtain a water phase; s2, preparing an oil phase containing a surfactant; s3, under the stirring condition, dropwise adding the water phase into the oil phase at a constant speed, and fully emulsifying and cross-linking the mixture by using homogeneous emulsification equipment to form a W / O solution; s4, adding a cross-linking agent II into the W / O solution, and fully cross-linking to obtain a cured product; and S5, washing and drying the cured product to obtain the product. The cross-linking agent is added by adopting a two-step method, the cross-linking agent is firstly added into the water phase, then the water phase and the oil phase are mixed, and then the cross-linking agent is added, so that the prepared glucan microspheres are good in morphology, relatively low in dry sphere water absorption (relatively high in solid content) and slow in in-vitro degradation. And the prepared microspheres are round and full in appearance, controllable in particle size and slow in in-vitro degradation, and have good biological safety, stability and clinical application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to A61K and the field of drug preparations, and in particular to a method for preparing dextran microspheres and the prepared dextran microspheres. Background Art

[0002] Dextran is a linear polysaccharide formed by the polymerization of multiple glucose molecules. It has a high molecular weight. The dextran molecular chain contains a large number of hydroxyl groups, which has good biocompatibility with biological tissues. The cross-linked network structure in dextran can be used as a molecular sieve, a drug carrier, and can achieve drug filling. Existing methods for preparing dextran microspheres include microemulsion polymerization or chemical cross-linking, but the oil phase used in the microemulsion polymerization process usually causes serious environmental pollution, and the small droplets formed will agglomerate to varying degrees. The particle size range of the microspheres is large, and the practical performance is not high. In addition, the existing dextran microspheres are usually degraded by swelling, and the microspheres will produce fragments after swelling, which is not conducive to subsequent treatment recovery.

[0003] Chinese invention patent CN201110144320.0 discloses a hydrophilic porous dextran-based microsphere and a preparation method thereof, using epichlorohydrin as a cross-linking agent and Span 80 as a dispersant, and synthesizing cross-linked dextran gel microspheres with a spatial network structure by reverse suspension polymerization. The pores of the prepared porous microspheres can accommodate a large amount of free water, which plays a role in coating water-soluble drugs. However, chlorobenzene is used as the oil phase, which seriously pollutes the environment and harms human health, and the droplets formed are small in size and easy to agglomerate. Chinese invention patent CN201510404680.8 discloses a preparation method of dextran microsphere gel, wherein the dispersed phase solution is uniformly added to the continuous phase solution, and the mixture is fully emulsified by a homogenizing emulsifying device; a cross-linking agent is added, and the mixture is fully cross-linked by mechanical stirring to obtain a dextran microsphere gel, which is simple in process and can be mass-produced without safety hazards, but the vegetable oil is used as the oil phase, and the gel microspheres formed are not easy to wash and require a large amount of water to rinse. Summary of the invention

[0004] In order to develop a method for preparing dextran microspheres that is pollution-free, non-agglomerated, has a stable process, and is easy to operate, and to form dextran microspheres with rounded morphology, uniform particle size, and slow degradation, the first aspect of the present invention provides a method for preparing dextran microspheres, comprising the following steps:

[0005] S1 prepares a sodium hydroxide aqueous solution containing crosslinking agent I and dextran to obtain an aqueous phase;

[0006] S2 prepares an oil phase containing a surfactant;

[0007] S3, under stirring conditions, the water phase is added dropwise to the oil phase at a uniform speed, and a homogenizing emulsifier is used to fully emulsify and cross-link the mixture to form a W / O solution;

[0008] S4: adding crosslinking agent II to the W / O solution to fully crosslink and obtain a cured product;

[0009] S5: washing the solidified product and drying it.

[0010] As a preferred embodiment, the method for preparing the dextran microspheres comprises the following steps:

[0011] S1 weighs dextran, dissolves it in a sodium hydroxide aqueous solution, stirs until the dextran is completely dissolved into a colorless transparent solution, then adds crosslinking agent I, and dissolves uniformly to obtain an aqueous phase;

[0012] S2 weighs a surfactant and adds it to the oil phase, stirring until the surfactant is completely dissolved to obtain an oil phase;

[0013] S3, under stirring, uniformly add the water phase to the oil phase, and use a homogenizing emulsifier to fully emulsify the mixture for 40-80 minutes to form a W / O solution;

[0014] S4: adding crosslinking agent II to the W / O solution, fully crosslinking, the crosslinking time is greater than 12h, and a cured product is obtained;

[0015] S5: washing the solidified product and drying it.

[0016] As a preferred embodiment, the specific method of washing is: adding ethanol aqueous solution to the solidified product and stirring, washing 4-5 times, sieving, and then repeatedly washing with ultrapure water, and finally filtering to remove surface moisture to obtain dextran microsphere gel.

[0017] As a preferred embodiment, the mass concentration of the ethanol aqueous solution is 50wt%.

[0018] As a preferred embodiment, the specific method of drying is: freeze-drying the dextran microsphere gel for 23-25 ​​hours to form a dry powder.

[0019] As a preferred embodiment, the weight ratio of the crosslinking agent I to the crosslinking agent II is (10-20): (80-90).

[0020] As a preferred embodiment, the weight ratio of the crosslinking agent I to the crosslinking agent II is (13-17): (83-87).

[0021] As a preferred embodiment, the weight ratio of the crosslinking agent I to the crosslinking agent II is 15:85.

[0022] As a preferred embodiment, the average molecular weight of the dextran is 40000-100000 Da, and the mass fraction of the dextran is 40-70%.

[0023] As a preferred embodiment, the mass fraction of the dextran is 50-65%, and more preferably, the mass fraction of the dextran is 60%.

[0024] As a preferred embodiment, the molar concentration of the sodium hydroxide aqueous solution is 2-3.5M.

[0025] As a preferred embodiment, the molar concentration of the sodium hydroxide aqueous solution is 2.5-3M, and more preferably, the molar concentration of the sodium hydroxide aqueous solution is 3M.

[0026] As a preferred embodiment, the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is (0.5-3):1.

[0027] As a preferred embodiment, the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is (1-2.5):1.

[0028] As a preferred embodiment, the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 2:1.

[0029] The applicant found in the experiment that the cross-linked dextran microspheres formed by reacting with 60% glucose in a 3M sodium hydroxide aqueous solution had a rounded morphology, uniform particle size, and slow degradation. The possible reason is that the non-toxic liquid paraffin used as the reaction system in this application makes the formed dextran microspheres easy to agglomerate, and the microsphere particle size regulation and distribution are uneven. In this application, the concentration of the aqueous solution of dextran and sodium hydroxide is controlled, the concentration of the cross-linking agent is regulated, and the oil-water ratio is balanced to balance the particle size and degradation degree of the dextran microspheres, so that the particle size is uniform and not easy to agglomerate, and the degradation time is extended. In this application, the use of dextran and sodium hydroxide solution under the preferred conditions can avoid the problem that the cross-linking speed of the dextran microspheres is too fast, which causes the problem that the microspheres cannot be completely cross-linked, resulting in incomplete cross-linking.

[0030] The applicant further discovered that by adding a cross-linking agent in a two-step method, the formed dextran microspheres can absorb less dry water and have a higher solid content. In addition, the microspheres shrink and degrade from the outside to the inside, are not easy to migrate, and are easy to stimulate collagen regeneration in the surrounding environment.

[0031] As a preferred embodiment, the surfactant is a nonionic surfactant, and the nonionic surfactant is selected from at least one of Span 20, Span 80, and Span 85.

[0032] As a preferred embodiment, the nonionic surfactant is Span 80.

[0033] As a preferred embodiment, the mass fraction of the nonionic surfactant is 3%-10%, and more preferably, the mass fraction of the nonionic surfactant is 6%.

[0034] As a preferred embodiment, the volume ratio of the water phase to the oil phase is 1:(7.5-20).

[0035] As a preferred embodiment, the volume ratio of the water phase to the oil phase is 1:(10-20).

[0036] As a preferred embodiment, the volume ratio of the water phase to the oil phase is 1:15.

[0037] As a preferred embodiment, the reaction conditions in step S4 are: cross-linking temperature 30-70°C.

[0038] As a preferred embodiment, the reaction conditions in step S4 are: cross-linking temperature 30-50°C.

[0039] As a preferred embodiment, the reaction conditions in step S4 are: cross-linking temperature 40°C.

[0040] As a preferred embodiment, the oil phase is liquid paraffin, and the crosslinking agent I and the crosslinking agent II are both selected from at least one of epichlorohydrin, acrylamide, N,N-methylene acrylamide, and glutaraldehyde.

[0041] As a preferred embodiment, the oil phase is liquid paraffin, and the crosslinking agent I and the crosslinking agent II are both epichlorohydrin.

[0042] The second aspect of the present invention provides a dextran microsphere, which is prepared by the above-mentioned method for preparing dextran microsphere.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The preparation method of the dextran microspheres of the present invention adopts a two-step method to add a crosslinking agent, first adding the crosslinking agent to the aqueous phase, and then adding the crosslinking agent after the aqueous phase and the oil phase are mixed. The prepared dextran microspheres have good morphology, less dry ball water absorption (higher solid content), and slow in vitro degradation of the microspheres.

[0045] (2) In the method for preparing the dextran microspheres of the present invention, the cross-linking temperature of step S4 is 40° C., so that the reactants can be effectively mixed, which is beneficial to the cross-linking reaction, reduces the generation of by-products and product degradation, and the prepared microspheres have a rounded morphology and are free of agglomeration.

[0046] (3) The method for preparing the dextran microspheres of the present invention adopts a volume ratio of the oil phase to the water phase of 1: (7.5-20), and the microspheres formed have a suitable particle size, are not easy to agglomerate, and have a uniform particle size.

[0047] (4) The preparation method of the dextran microspheres described in the present invention uses glucose with a mass concentration of 60% to react in a 3M sodium hydroxide aqueous solution. The prepared microspheres have a rounded morphology, controllable particle size, slow in vitro degradation, and good biosafety, stability and clinical application prospects.

[0048] (5) In the method for preparing dextran microspheres of the present invention, the total mass of crosslinker I and crosslinker II is in a mass ratio of (0.5-3):1 with respect to dextran. The prepared microspheres have low water absorption, and the method has stable process and simple operation. The raw materials are inexpensive, the process is simple and can be mass-produced, and there are no hidden dangers of production safety and environmental pollution. The method can be widely used in different technical fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The in vitro degradation line graph of the dextran microspheres prepared in Examples 11, 16, 17, and 18;

[0050] Figure 2 is the morphology of the microspheres of Example 11;

[0051] Figure 3 This is the microsphere morphology of Comparative Example 1;

[0052] Figure 4 This is a 2-day in vitro degradation graph of the dextran microspheres prepared in Example 21;

[0053] Figure 5 This is the in vitro degradation diagram of the dextran microspheres prepared in Comparative Example 1 for 2 days. DETAILED DESCRIPTION

[0054] Example 1

[0055] A method for preparing dextran microspheres comprises the following steps:

[0056] S1 weighed dextran and dissolved it in 100 mL of sodium hydroxide aqueous solution, stirred until the dextran was completely dissolved into a colorless transparent solution, then added crosslinking agent I, stirred at 300 rpm for 30 min until it was evenly dissolved to obtain an aqueous phase;

[0057] S2 weighed 60 g of surfactant and added it to 1000 mL of oil phase, and stirred at 300 rpm for 30 min until the surfactant was completely dissolved to obtain an oil phase;

[0058] S3, under stirring conditions, the temperature was controlled at 25°C, the water phase was uniformly added to the oil phase, and the mixture was fully emulsified using a homogenizing emulsifier, and the emulsification was performed at 300 rpm for 60 min to form a W / O solution;

[0059] S4: adding crosslinking agent II to the W / O solution, fully crosslinking, the crosslinking time is greater than 12h, and a cured product is obtained;

[0060] S5: washing the solidified product and drying it.

[0061] The specific method of washing is: adding ethanol aqueous solution to the solidified product and stirring, washing 4-5 times, sieving, and then repeatedly washing with ultrapure water, and finally filtering to remove surface water to obtain the dextran microsphere gel.

[0062] The mass concentration of the ethanol aqueous solution is 50wt%.

[0063] The specific drying method is: freeze-drying the dextran microsphere gel for 24 hours to form a dry powder.

[0064] The weight ratio of the crosslinking agent I to the crosslinking agent II is 15:85.

[0065] The average molecular weight of the dextran is 700000 Da, and the mass fraction of the dextran is 40%. Purchased from: Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 9004-54-0.

[0066] The molar concentration of the sodium hydroxide aqueous solution is 2.5M.

[0067] The mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 1:1.

[0068] The surfactant is Span 80.

[0069] The volume ratio of the water phase to the oil phase is 1:15.

[0070] The reaction conditions in step S4 are: cross-linking temperature 40°C.

[0071] The oil phase is liquid paraffin, purchased from Shanghai Titan Technology Co., Ltd., CAS: 8012-95-1. The crosslinking agent I and the crosslinking agent II are both epichlorohydrin.

[0072] Example 2

[0073] A method for preparing dextran microspheres, the specific implementation manner is the same as that of Example 1, except that the mass fraction of the dextran is 50%.

[0074] Example 3

[0075] A method for preparing dextran microspheres, the specific implementation manner is the same as that of Example 1, except that the mass fraction of the dextran is 60%.

[0076] Example 4

[0077] A method for preparing dextran microspheres, the specific implementation manner is the same as that of Example 1, except that the mass fraction of the dextran is 70%.

[0078] Example 5

[0079] A method for preparing dextran microspheres, the specific implementation manner is the same as that of Example 1, except that the mass fraction of the dextran is 80%.

[0080] Example 6

[0081] A method for preparing dextran microspheres, the specific implementation method is the same as Example 3, except that the molar concentration of the sodium hydroxide aqueous solution is 2M.

[0082] Example 7

[0083] A method for preparing dextran microspheres, the specific implementation method is the same as Example 3, except that the molar concentration of the sodium hydroxide aqueous solution is 3M.

[0084] Example 8

[0085] A method for preparing dextran microspheres, the specific implementation method is the same as Example 3, except that the molar concentration of the sodium hydroxide aqueous solution is 3.5M.

[0086] Example 9

[0087] A method for preparing dextran microspheres, the specific implementation method is the same as Example 7, except that the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 2:3.

[0088] Example 10

[0089] A method for preparing dextran microspheres, the specific implementation method is the same as Example 7, except that the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 1.5:1.

[0090] Embodiment 11

[0091] A method for preparing dextran microspheres, the specific implementation method is the same as Example 7, except that the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 2:1.

[0092] Example 12

[0093] A method for preparing dextran microspheres, the specific implementation method is the same as Example 7, except that the mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 3:1.

[0094] Example 13

[0095] A method for preparing dextran microspheres, the specific implementation method is the same as Example 11, except that the volume ratio of the water phase to the oil phase is 1:10.

[0096] Embodiment 14

[0097] A method for preparing dextran microspheres, the specific implementation method is the same as Example 11, except that the volume ratio of the water phase to the oil phase is 1:7.5.

[0098] Embodiment 15

[0099] A method for preparing dextran microspheres, the specific implementation method is the same as Example 11, except that the volume ratio of the water phase to the oil phase is 1:20.

[0100] Example 16

[0101] A method for preparing dextran microspheres, the specific implementation method is the same as Example 11, except that the reaction conditions in step S4 are: cross-linking temperature 30°C.

[0102] Embodiment 17

[0103] A method for preparing dextran microspheres, the specific implementation method is the same as Example 11, except that the reaction conditions in step S4 are: cross-linking temperature 50°C.

[0104] Embodiment 18

[0105] A method for preparing dextran microspheres, the specific implementation method is the same as Example 11, except that the reaction conditions in step S4 are: cross-linking temperature 70°C.

[0106] Embodiment 19

[0107] A method for preparing dextran microspheres comprises the following steps:

[0108] S1 weighed dextran and dissolved it in 100 mL of sodium hydroxide aqueous solution, stirred until the dextran was completely dissolved into a colorless transparent solution, and stirred at 300 rpm for 30 min to obtain an aqueous phase after the solution was uniformly dissolved;

[0109] S2 weighed 60 g of surfactant and added it to 1000 mL of oil phase, and stirred at 300 rpm for 30 min until the surfactant was completely dissolved to obtain an oil phase;

[0110] S3, under stirring conditions, the temperature was controlled at 25°C, the water phase was uniformly added to the oil phase, and the mixture was fully emulsified using a homogenizing emulsifier, and the emulsification was performed at 300 rpm for 60 min to form a W / O solution;

[0111] S4: adding a crosslinking agent to the W / O solution, fully crosslinking, the crosslinking time is greater than 12 hours, and a cured product is obtained;

[0112] S5: washing the solidified product and drying it.

[0113] The specific method of washing is: adding ethanol aqueous solution to the solidified product and stirring, washing 4-5 times, sieving, and then repeatedly washing with ultrapure water, and finally filtering to remove surface water to obtain the dextran microsphere gel.

[0114] The mass concentration of the ethanol aqueous solution is 50wt%.

[0115] The specific drying method is: freeze-drying the dextran microsphere gel for 24 hours to form a dry powder.

[0116] The average molecular weight of the dextran is 700000 Da, and the mass fraction of the dextran is 60%.

[0117] The molar concentration of the sodium hydroxide aqueous solution is 3M.

[0118] The mass ratio of the cross-linking agent to dextran is 2:1.

[0119] The surfactant is Span 80.

[0120] The volume ratio of the water phase to the oil phase is 1:15.

[0121] The reaction conditions in step S4 are: cross-linking temperature 40°C.

[0122] The oil phase is liquid paraffin, and the cross-linking agent is epichlorohydrin.

[0123] Embodiment 20

[0124] A method for preparing dextran microspheres comprises the following steps:

[0125] S1 weighed dextran and dissolved it in 100 mL of sodium hydroxide aqueous solution, stirred until the dextran was completely dissolved into a colorless transparent solution, and stirred at 300 rpm for 30 min to obtain an aqueous phase after the solution was uniformly dissolved;

[0126] S2 weighed 60 g of surfactant and added it to 1000 mL of oil phase, added crosslinking agent, and stirred at 300 rpm for 30 min until completely dissolved to obtain oil phase;

[0127] S3, under stirring conditions, the temperature was controlled at 25°C, the water phase was uniformly added to the oil phase, and the mixture was fully emulsified using a homogenizing emulsifier, and the emulsification was performed at 300 rpm for 60 min to form a W / O solution;

[0128] S4 waits for the W / O solution to be fully cross-linked, the cross-linking time is greater than 12 hours, and a cured product is obtained;

[0129] S5: washing the solidified product and drying it.

[0130] The specific method of washing is: adding ethanol aqueous solution to the solidified product and stirring, washing 4-5 times, sieving, and then repeatedly washing with ultrapure water, and finally filtering to remove surface water to obtain the dextran microsphere gel.

[0131] The mass concentration of the ethanol aqueous solution is 50wt%.

[0132] The specific drying method is: freeze-drying the dextran microsphere gel for 24 hours to form a dry powder.

[0133] The average molecular weight of the dextran is 700000 Da, and the mass fraction of the dextran is 60%.

[0134] The molar concentration of the sodium hydroxide aqueous solution is 3M.

[0135] The mass ratio of the cross-linking agent to dextran is 2:1.

[0136] The surfactant is Span 80.

[0137] The volume ratio of the water phase to the oil phase is 1:15.

[0138] The reaction conditions in step S4 are: cross-linking temperature 40°C.

[0139] The oil phase is liquid paraffin, and the cross-linking agent is epichlorohydrin.

[0140] Embodiment 21

[0141] A method for preparing dextran microspheres comprises the following steps:

[0142] S1 weighed dextran and dissolved it in 100 mL of sodium hydroxide aqueous solution, stirred until the dextran was completely dissolved into a colorless transparent solution, then added crosslinking agent I, stirred at 300 rpm for 30 min until it was evenly dissolved to obtain an aqueous phase;

[0143] S2 weighed 60 g of surfactant and added it to 1000 mL of oil phase, and stirred at 300 rpm for 30 min until the surfactant was completely dissolved to obtain an oil phase;

[0144] S3, under stirring conditions, the temperature was controlled at 25°C, the water phase was uniformly added to the oil phase, and the mixture was fully emulsified using a homogenizing emulsifier, and the emulsification was performed at 300 rpm for 60 min to form a W / O solution;

[0145] S4: adding crosslinking agent II to the W / O solution, fully crosslinking, the crosslinking time is greater than 12h, and a cured product is obtained;

[0146] S5: washing the solidified product and drying it.

[0147] The specific method of washing is: adding ethanol aqueous solution to the solidified product and stirring, washing 4-5 times, sieving, and then repeatedly washing with ultrapure water, and finally filtering to remove surface water to obtain the dextran microsphere gel.

[0148] The mass concentration of the ethanol aqueous solution is 50wt%.

[0149] The specific drying method is: freeze-drying the dextran microsphere gel for 24 hours to form a dry powder.

[0150] The weight ratio of the crosslinking agent I to the crosslinking agent II is 6:34.

[0151] The average molecular weight of the dextran is 700000 Da, and the mass fraction of the dextran is 60%.

[0152] The molar concentration of the sodium hydroxide aqueous solution is 3M.

[0153] The mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is 2:1.

[0154] The surfactant is Span 80.

[0155] The volume ratio of the water phase to the oil phase is 1:15.

[0156] The reaction conditions in step S4 are: cross-linking temperature 40°C.

[0157] The oil phase is liquid paraffin, and the crosslinking agent I and the crosslinking agent II are both epichlorohydrin.

[0158] Comparative Example 1

[0159] Commercially available dextran microspheres.

[0160] The dextran gel microspheres were purchased from McLean Reagent Network, CAS: 9041-35-4, model G25.

[0161] Performance Testing

[0162] 1. Light microscopy test

[0163] The morphology of the dextran microspheres prepared in Example 11 and Comparative Example 1 was observed using a WD300-48LT biological microscope. Figure 2 The microsphere morphology of the dextran microspheres of Comparative Example 1 is shown in Figure 3 .

[0164] 2. Dry-bulb water absorption test

[0165] (1) Take a certain amount of wet dextran microspheres (100-300 μm) and use filter paper to absorb the moisture on the surface of the microspheres;

[0166] (2) Accurately weigh the wet microspheres m in (1) above. 0 Put it in the oven, set the oven temperature to 60℃, take out the dried microspheres after 24 hours, weigh them, and record them as m 1

[0167] (3) Calculate the water absorption of microspheres: m 0 / m 1

[0168] The test results are shown in Table 1.

[0169] 3. In vitro degradation test

[0170] (1) Weigh 1g (W 0 ) Wet dextran microspheres (100-300 μm) product into a 15 mL centrifuge tube of known weight, and weigh the wet microsphere product + centrifuge tube weight (W 1 );

[0171] (2) Add 5 mL of 50 mg / mL α-glucanase solution to the centrifuge tube in (1) above, seal it, and place the centrifuge tube in a constant temperature shaker (40 rpm) at 37°C;

[0172] (3) Samples were taken out at regular intervals (1, 3, 6, and 8 days), centrifuged (4000 rpm, 3 min), and the supernatant was separated. The weight of the sample + centrifuge tube (W) was then weighed. i ) until the end of the experiment;

[0173] (4) Calculate the degradation rate of the microsphere product according to the following formula, and draw a curve showing the relationship between the degradation rate and the hydrolysis time;

[0174]

[0175] Where, H: degradation rate (%); W i : mass of wet bulb sample + centrifuge tube after degradation for i days (g); W 1 : Initial wet bulb sample + centrifuge tube mass (g).

[0176] Test results see Figure 1 In the figure: A. Example 11; B. Example 16; C. Example 17; D. Example 18.

[0177] The in vitro degradation of the dextran microspheres prepared in Example 21 for 2 days is shown in Figure 4 The in vitro degradation of the dextran microspheres prepared in Comparative Example 1 for 2 days is shown in Figure 5 .

[0178] Table 1

[0179] Dry ball water absorption (g / g) Example 1 5.7 Example 2 5.4 Example 3 5.06 Example 4 5.35 Example 5 5.9 Example 6 / Example 7 3.3 Example 8 / Example 9 3.21 Example 10 3.2 Embodiment 11 3.06 Example 12 3.67 Example 13 3.66 Embodiment 14 / Embodiment 15 6.25 Example 16 4.6 Embodiment 17 6.09 Embodiment 18 6.59 Embodiment 19 3.2 Embodiment 20 3.5 Embodiment 21 3

[0180] It can be seen from the test results of Examples 1 to 5 that: as the mass percentage concentration of dextran increases, the particle size of the prepared microspheres gradually increases. When the mass percentage concentration of dextran is greater than 60%, due to the high overall viscosity of the aqueous phase, the aqueous phase dissolves unevenly and the loss during transfer is large. When the mass percentage concentration of dextran is 60%, the prepared microspheres have a rounded morphology and a particle size of 100-300 μm.

[0181] In addition, the in vitro degradation of dextran microspheres prepared with different concentrations of dextran was significantly different. When the concentration of dextran was higher than 70%, the prepared microspheres degraded faster in vitro. This may be because when the concentration of dextran was high, the speed at which dextran was converted into microspheres was accelerated, resulting in cross-linking on the surface of the microspheres, but the inside of the microspheres was not completely cross-linked. Therefore, the initial in vitro degradation of the microspheres was slow, and as time went on, the inside of the microspheres quickly degraded completely.

[0182] When the concentration of dextran is lower than 50%, the particle size of the prepared microspheres is smaller, the water absorption of the microspheres is higher, and the in vitro degradation is faster. This may be because the microspheres are not fully cross-linked due to the low concentration of dextran, and the overall cross-linking degree is low, so the microspheres degrade faster in vitro.

[0183] Through the test results of Example 3 and Examples 6-8, it can be seen that: when the concentration of sodium hydroxide is lower than 2.5M, dextran is not completely converted into microspheres, and the yield of microspheres is low; when the concentration of sodium hydroxide is 3.5M, the prepared microspheres agglomerate and have poor morphology; when the concentration of sodium hydroxide is 3M, the prepared microspheres have a round morphology, no agglomeration, and the dry ball water absorption is 3.3.

[0184] Through the test results of Example 7, Examples 9-11, it can be seen that: when the mass ratio of epichlorohydrin to dextran raw materials is lower than 1, the prepared microspheres have a higher water absorption, and the dry ball water absorption is greater than 5; when the mass ratio of epichlorohydrin to dextran raw materials is higher than 2, the prepared microspheres have a lower water absorption, and the dry ball water absorption is less than 3, but the microspheres are easy to agglomerate; when the mass ratio of epichlorohydrin to dextran raw materials is 2, the prepared microspheres have a better morphology, uniform particle size, and a dry ball water absorption of 3.06.

[0185] Through the test results of Example 11 and Examples 13-15, it can be seen that: when the water-oil ratio is lower than 1:15, the prepared microspheres are prone to agglomeration; when the water-oil ratio is 1:20, the particle size of the prepared microspheres is relatively small; when the water-oil ratio is 1:15, the prepared microspheres have a better morphology, uniform particle size, no agglomeration, and the dry ball water absorption is 3.06.

[0186] Through the test results of Example 11 and Examples 16-18, it can be seen that when the cross-linking temperature is higher than 50°C, the cross-linking degree and morphology of the prepared microspheres are poor; when the cross-linking temperature is 40°C, the prepared microspheres have a round morphology without agglomeration, and the dry ball water absorption is between 2.8-3.2.

[0187] Crosslinking temperature is one of the important factors affecting the rate of chemical reaction. Within a certain range, as the crosslinking temperature increases, the degree of crosslinking may increase, because high temperature helps the reactant molecules to fully contact and react. However, when the temperature exceeds a certain limit, excessively high temperature may cause excessive crosslinking and produce some side reactions.

[0188] Under normal circumstances, the reaction temperature for cross-linking of dextran and epichlorohydrin is generally between 30°C and 40°C, which is conducive to the effective mixing of the reactants and the cross-linking reaction. When the reaction temperature is greater than 40°C, the reaction rate can be accelerated, but side reactions or product degradation are prone to occur. When the temperature is too low, it may lead to insufficient cross-linking, resulting in product performance that does not meet the requirements.

[0189] The test results of Examples 19-21 show that when epichlorohydrin is added by the two-step method, the prepared dextran microspheres have good morphology, less dry ball water absorption (higher solid content), and the microspheres degrade slowly in vitro.

[0190] By comparing Example 11 and Comparative Example 1, it was found that the dextran microspheres prepared in Example 11 had a rounded morphology and uniform particle size, while the microspheres prepared in Comparative Example 1 had an uneven particle size.

[0191] Through the in vitro degradation diagram, it was found that the degradation of the microspheres prepared in Example 11 was gradual from the outside to the inside, the microspheres gradually became smaller, and finally completely degraded; at the beginning of the degradation of the microspheres in Comparative Example 1, the particle size of the microspheres did not decrease, but gradually swelled, and finally degraded and broke, producing a lot of fragments.

[0192] Through the analysis of particle size and in vitro degradation data, it is speculated that due to the different particle sizes and degradation of Example 11 and Comparative Example 1, the particle size of the microspheres prepared in Example 1 is relatively uniform, and the microspheres are gradually degraded from the outside to the inside, so that the microspheres are more likely to stimulate collagen regeneration when injected into the body, resulting in the microspheres being less likely to migrate; while the particle size of the microspheres in Comparative Example 1 is not uniform, and during the degradation process, due to the gradual increase in volume, less collagen may be stimulated and produced around the microspheres, making the microspheres more likely to migrate.

Claims

1. A method for preparing dextran microspheres, characterized in that: The following steps are involved: S1 prepares a sodium hydroxide aqueous solution containing crosslinker I and dextran to obtain an aqueous phase; S2 prepares an oil phase containing a surfactant; S3, under stirring conditions, the water phase is added dropwise to the oil phase at a uniform speed, and the mixture is fully emulsified using a homogenizing emulsifier to form a W / O solution; S4: adding crosslinking agent II to the W / O solution to fully crosslink and obtain a cured product; S5: washing the solidified product and drying it.

2. The method for preparing dextran microspheres according to claim 1, characterized in that: The weight ratio of the crosslinking agent I to the crosslinking agent II is (10-20): (80-90).

3. The method for preparing dextran microspheres according to claim 1, characterized in that: The average molecular weight of the dextran is 40000-100000 Da, and the mass fraction of the dextran is 40-70%.

4. The method for preparing dextran microspheres according to claim 1, characterized in that: The molar concentration of the sodium hydroxide aqueous solution is 2-3.5M.

5. The method for preparing dextran microspheres according to claim 1, characterized in that: The mass ratio of the total mass of the cross-linking agent I and the cross-linking agent II to the mass of the dextran is (0.5-3):

1.

6. The method for preparing dextran microspheres according to claim 1, characterized in that: The surfactant is a nonionic surfactant, and the nonionic surfactant is selected from at least one of Span 20, Span 80, and Span 85.

7. The method for preparing dextran microspheres according to claim 1, characterized in that: The volume ratio of the water phase to the oil phase is 1:(7.5-20).

8. The method for preparing dextran microspheres according to claim 1, characterized in that: The reaction conditions in step S4 are: cross-linking temperature 30-70°C.

9. The method for preparing dextran microspheres according to claim 1, characterized in that: The oil phase is liquid paraffin, and the crosslinking agent I and the crosslinking agent II are both selected from at least one of epichlorohydrin, acrylamide, N,N-methylene acrylamide, and glutaraldehyde.

10. A dextran microsphere, characterized in that: The dextran microspheres are prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • A hydrophilic porous dextran-based microsphere and its preparation method

    CN102258787A

  • A method for preparing dextran microsphere gel

    CN105153440B

Cited By

  • Embolization microsphere for chronic musculoskeletal system pain control and preparation method and application thereof

    CN121714749A